Taxonomic nomenclature what's in a name -- theory and history - Pavlinov, I︠A︡. (Igorʹ I︠A︡kovlevich) (CRC Press, an imprint of Taylor & Francis Group, LLC, 2022)
"This book a conceptual examination of the role of nomenclature in systematics. It is not just another "instruction for use" of the nomenclature codes. The goal is to review theoretical foundations of taxonomic nomenclature and historical development of its fundamental regulating features"--Provided by publisher.